Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.